Peningkatan Pengetahuan dan Keterampilan Menulis Puisi Melalui Pendekatan Contextual Teaching and Learning pada Siswa SD Inpres Tela Kabupaten Maluku Barat Daya - Dovila Dovila Johansz; Meisya Onarely (Universitas Muhammadiyah Purwokerto, 2023)
Writing poetry is an activity that requires knowledge and skills. The contextual teaching and learning (CTL) model is used as a learning concept that connects students' knowledge with its application in everyday life, linking learning to the environment around students which is divided into 2 cycles. The first cycle uses the lecture model and the second cycle uses the CTL model. The number of respondents who participated in this study were 28 students. It was concluded that the Contextual Teaching and Learning (CTL) learning model proved effective in increasing the knowledge and skills of writing poetry for the fifth grade students of SD Inpres Tela, Southwest Maluku Regency by 79%.